Current Insights into Phytochemistry, Nutritional, and Pharmacological Properties of Prosopis Plants. (11th March 2022) - Zhong, Jianshu; Lu, Peiyao; Wu, Hanjing; Liu, Ziyao; Sharifi-Rad, Javad; Setzer, William N.; Suleria, Hafiz A.R.
Abstract : Prosopis is a regional cash crop that is widely grown in arid, semiarid, tropical, and subtropical areas. Compared with other legume plants, Prosopis is underutilized and has great potentialities. Prosopis not only is a good source of timber, construction, fencing material, and gum, but also can be applied for food, beverage, feed, and medicine. Prosopis contains numerous phytochemical constituents, including carbohydrates, proteins, fatty acids, minerals, and vitamins, while varieties of phenolic compounds have also been identified from different parts of Prosopis . Flavonoids (especially C -glycosyl flavonoids), tannins, catechin, 4′-O-methyl-gallocatechin, mesquitol, and quercetin O -glycosides are significant phenolic contents in Prosopis . Various extracts of Prosopis displayed a wide range of biological properties, such as antioxidant, antihyperglycemic, antibacterial, anthelmintic, antitumor, and anticancer. Additionally, Prosopis has the potential to be an ideal diet that contains abundant dietary fiber, minerals, galactomannans, and low-fat content. However, the bioactivity and pharmacological properties associated with Prosopis were influenced by the bioavailability of phytochemicals, various antinutritional compounds, and the interactions of protein and phenolic compounds. The bioavailability of Prosopis is mainly affected by phenolic contents, especially catechin. The antinutritional compounds negatively affect the nutritional qualities of Prosopis, which can be prevented by heating. The protein-phenolic compound interactions can help the human body to absorb quercetin from Prosopis . This literature review aimed to provide systematic information on the physical, biochemical, pharmacological, and nutritional properties and potential applications of Prosopis .